OP0254 Association Between Dickkopf-1 Levels, 25-Hydroxyvitamin D Status and Bone Mineral Density in Postmenopausal Patients with Systemic Sclerosis. (9th June 2015) - Seriolo, B.; Casabella, A.; Paolino, S.; Botticella, G.; Meroni, M.; Seriolo, C.; Molfetta, L.
Abstract : Background: Patients affected by systemic sclerosis (SSc) might present an increased risk of low bone mass as a result of multisystemic disorder such as gut malabsorption or malnutrition and decreased activation of vitamin D in the altered fibrotic skin 1 . Dickkopf-1 (Dkk-1) is recognized as a key regulator of bone remodeling by inhibition of the Wnt signalling requiare for new bone formattino and is increased in postmenopausal patients. Objectives: In this study, bone mineral density (BMD), 25-hydroxyvitamin D [25(OH) D] status and Dkk-1 levels were evaluated in order to investigate in SSc patients the incidence of osteoporosis and/or osteopenia, in according to their different nailfold videocapillaroscopic (NVC) microangiopathy pattern (namely "Early", "Active", and "Late"). Methods: Seventy-four postmenopausal patients (mean age 64±3 years) affected by SSc ("early" n=12; "active" n=21 and "late" pattern n=41) and 63 age-matched healthy controls (mean age 63±5 years) were studied. BMD (g/cm 2 ) of the lumbar spine (L1 -L4 ) and of the proximal femur (femoral neck, and total hip) was analyzed using dual-energy X-ray absorptiometry (DXA) scan (Lunar Prodigy, GE, USA). Dkk-1 serum levels were measured using an enzyme-linked immunosorbent assay and 25(OH)D serum levels were evaluated by radioimmunoassay. Vitamin D levels were classified as normal (>30 ng/ml), insufficient (<30 and >10 ng/ml), and deficient <10 ng/ml) The statistical analysis was performed by non-parametric tests. Results: Out of 74 enrolled patients with SSc, 56 (76%) presented bone loss; in particular 32 (43%) showed osteoporosis and 24 (32%) osteopenia. BMD was found significantly lower in SSc patients than in control group (lumbar spine: 0.890±0.21 g/cm 2 vs 1.028±0.26 g/cm 2 ; femoral neck 0.698±0.21 g/cm 2 vs 0.855±0.23 g/cm 2 ; total hip 0.801±0.14 g/cm 2 vs 0.922±0.19 g/cm 2, overall significance p<0.001). DKK-1 levels were significantly higher in SSc patients than in control group (2734±894 pg/mL vs 2044±692 pg/mL, p<0.007). Vitamin D levels were found lower in SSc patients than in controls (18.6+ 31 ng/ml vs 42.8+ 23 ng/ml). Interestingly, BMD (lumbar spine 0.870±0.150 g/cm 2 vs 1.077±0.165 g/cm 2 ; total hip 0.660±0.246 g/cm 2 vs 0.783±0.113 g/cm 2 ) and 25(OH)D levels (9.3±2.3 ng/ml vs 16.8±3.6 ng/ml) were found lower and Dkk-1 levels (3265±666 pg/mL vs 2033±697 pg/mL) higher in patients with "late" pattern than "early"/"active" NVC patterns. Conclusions: This study showed a significant increase in serum levels of Dkk-1, associated with osteopenia/osteoporosis and deficient Vitamin D status in SSc patients with late NVC pattern when compared to healthy postmenopausal subjects. Interestingly, since Dkk-1 blocks activation and proliferation of established myofibroblasts in vitro and blocks pericyte proliferation to PDGF, pericyte migration, gene activation, and cytoskeletal reorganization to TGF-Î 2 or connective tissue growth factor (all activated in SSc), its increase observed in SSc patients is matter of further investigations 2, 3 . References: Cutolo M et al. Autoimmun Rev 2011:12;84-7 Ren S et al. Proc Natl Acad Sci U S A 2013;110:1440-5 Dees C et al. Ann Rheum Dis 2014:6;1232-9 Disclosure of Interest: None declared